Treatment of experimental periodontal disease by antimicrobial photodynamic therapy in nicotine-modified rats - Garcia, Valdir Gouveia [UNESP]; Fernades, Leandro Araújo [UNESP]; Macarini, Valmir Campos [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Martins, Thiago Marchi [UNESP]; Bosco, Alvaro Francisco [UNESP]; Nagata, Maria Jose Hitomi [UNESP]; Cirelli, Joni Augusto [UNESP]; Theodoro, Letícia Helena [UNESP] (Wiley, 2011)
Background The aim of this study was to compare antimicrobial photodynamic therapy (aPDT) as an adjunctive treatment to scaling and root planing (SRP) for induced periodontitis in nicotine-modified rats. Material & Methods A total of 240 rats were evenly divided into two groups: C – saline solution treatment; N – nicotine treatment. Periodontal disease was induced in both groups at the first mandibular molar. After 7 days, the ligature was removed. All animals were submitted to SRP and were divided according to the following treatments: SRP – irrigation with saline solution; Toluidine Blue-O (TBO) – irrigation with phenothiazinium dye (100 μg/ml); LLLT – laser irradiation (660 nm; 0.03 W; 4 J); and aPDT – TBO and laser irradiation. Ten animals in each group/treatment were euthanized at 7, 15 and 30 days. The histometric and immunohistochemical values were statistically analysed. Results Intragroup analysis demonstrated that in both groups the aPDT treatment resulted in lower bone loss (BL) when compared to SRP in all experimental periods. Intergroup analysis demonstrated that aPDT treatment resulted in lower BL in Group N than in Group C treated with SRP in all experimental periods. Conclusion Antimicrobial photodynamic therapy was an effective adjunctive treatment to SRP for induced periodontitis in nicotine-modified rats.
Keywords: Alveolar bone loss; Lasers; nicotine; Osteoclasts; Periodontitis; Photochemotherapy